Penghambatan Reaksi Maillard dari Ekstrak Buah Pisang Goroho Putih (Musa acuminata Colla) Sebagai Pencegahan Diabetes Mellitus - Randy Tampa'i (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
Indonesian natural products that are antioxidant have diversity and have not been used optimally, one of which is white goroho banana. White goroho banana (Musa acuminate Colla) is one of the endemic plants originating from North Sulawesi. These bananas are often used empirically as an additional / main food for people suffering from diabetes mellitus. This research aims to determine the potential inhibition of the Maillard reaction from extracts of white goroho banana by measuring the carbonyl protein content using a spectrophotometer. The result of this research is white goroho banana can used as inhibitor Maillard reaction to restrain Diabetes mellitus surface and grow. Acetone extract has the highest inhibitor Maillard reaction than ethanol and methanol. The activity of inhibitor Maillard reaction from acetone, ethanol and methanol extracts are 5,49; 3,18; 2,96%.Indonesian natural products that are antioxidant have diversity and have not been used optimally, one of which is white goroho banana. White goroho banana (Musa acuminate Colla) is one of the endemic plants originating from North Sulawesi. These bananas are often used empirically as an additional / main food for people suffering from diabetes mellitus. This research aims to determine the potential inhibition of the Maillard reaction from extracts of white goroho banana by measuring the carbonyl protein content using a spectrophotometer. The result of this research is white goroho banana can used as inhibitor Maillard reaction to restrain Diabetes mellitus surface and grow. Acetone extract has the highest inhibitor Maillard reaction than ethanol and methanol. The activity of inhibitor Maillard reaction from acetone, ethanol and methanol extracts are 5,49; 3,18; 2,96%.